Pendampingan terhadap Pelaku UMKM tentang Manfaat Teknologi Informasi Berbasis Ekonomi Syari’ah - Wijana, Miki; Nurkamali AZ, Ahmad; Zahra, Fazrin Rainy; Melly, Melly (Ma'soem University, 2025)
Cinangsi Village is one of the villages located in the Cisitu Subdistrict, Sumedang Regency. A portion of the community works as home-based entrepreneurs, commonly referred to as Micro, Small, and Medium Enterprises (MSMEs). The marketing of their products is still carried out in traditional ways and has not yet utilized digital technology tools that are currently trending. The most prominent issue faced by MSME actors is that they do not know where to start when it comes to online marketing, mainly due to limited skills and understanding of digital technology. Through an approach that involves socialization, participation, and implementation, a three-stage method was applied: the preparation stage, which includes field surveys and communication; the implementation stage, which involves assistance and guidance; and the evaluation stage, which reviews the outcomes achieved. As a result, MSME actors are now able to package their products with attractive designs, promote them through social media, and market them online through popular marketplaces visited by potential customers.